Os rótulos e estigmas como uma barreira na efetivação da empregabilidade das Pessoas com Deficiência - Boniholi, Gabriela Ishikawa (Universidade Federal de São Carlos, 2025)
The inclusion of people with disabilities in the labor market faces multiple barriers, which manifest in both institutional and organizational dimensions. These obstacles hinder the effective implementation of public policies and may include lack of accessibility, insufficient professional training, prejudice, and social stigma. This study was developed through the analysis of statements from different actors involved in the inclusion process — people with disabilities, their family members, representatives of hiring companies, and professionals from intermediary organizations. This is a qualitative research study, exploratory and descriptive in nature, with data collected through semi-structured interviews with 219 participants in six Brazilian cities selected for their prominent role in employability programs promoted by the Apaes. The results revealed that, although there have been advances and a growing recognition of the benefits of inclusion, prejudice still persists as a significant obstacle, often in subtle forms, influencing opportunities for hiring and career progression. Furthermore, the research highlighted the importance of considering family-related factors, the need to improve inclusion policies and management practices, and the crucial role of support organizations in developing more effective employability programs.
Stigma as a barrier to the effective employability of People with Disabilities
Keywords: Pessoas com Deficiência; Entraves; Estigma; Mercado de Trabalho; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO